International experiences and approaching ways to technology maps and technology roadmapping in Vietnam - Dung, Ta Viet; Hoang, Nguyen Duc (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Notions of technology maps and technology road-mapping are used largely in the world with many different approaching ways to them, subject to technological capabilities of every country as well as objectives of application for purpose of State administration and enterprise management. This paper summarizes different notions of technology maps and technology road-mapping which are in use and various types of technology roadmaps which are applied and developed largely in the world. At the same time, the paper provides an analysis of roles and necessity of technology road-mapping for S&T management activities as well as experiences of technology road-mapping and applications by developed countries such as the US, Canada, Japan, South Korea and some others. On basis of international experiences, the study team makes a deep analysis on approaching ways and contexts of development of models of technology roadmaps and road-mapping in the world. The paper also provides links between technology maps, technology roadmapping and technology innovation roadmaps. On basis of that, the study team proposes approaching ways in conformity to actual development context of Vietnam as technology late-comer, indicates clearly technology gaps to leading countries and sets up objectives of technology development to shorten existing technology gaps. Code: 16081801<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">